Existence conditions for self-orthogonal negacyclic codes over finite fields - Lin, Liren (2015)
In this paper, we obtain necessary and sufficient conditions for the nonexistence of nonzero self-orthogonal negacyclic codes over a finite field, of length relatively prime to the characteristic of the underlying field.